Skin manifestation in COVID-19 infection: a thousand appearances (immune response perspective) - Firmansyah, Yohanes; Elizabeth, Jessica; Tan, Sukmawati Tansil (International Journal of Research in Dermatology, 2020)
The clinical manifestations of COVID-19 infection are still unclear. The spectrum of the disease is very broad, with many target organs; one of them is skin. Various skin manifestations have been observed in COVID-19 patients. However, the observed skin manifestation was not specific. This following case series aims to provide an overview of skin manifestations in COVID-19 to help recognize the initial symptoms of COVID-19 infection. This case series also compares cases with and without skin manifestations. This case series discusses seven cases, which the patient had close contact, who had been diagnosed with confirmed COVID-19 by polymerise chain reaction (PCR) examination. The clinical symptoms were mild, such as fever, cough, sore throat, myalgia, malaise, headache, and skin lesions. There are few differences in in complete blood laboratories. Radiology features within normal limits. All patients were given a treatment regimen according to the Indonesian lung association recommendations and symptomatic drugs. Three of seven cases had skin manifestation, which two of them had a maculopapular lesion, and the other one had urticaria lesions. Subjective symptoms, such as itching and burning sensation, were reported. The majority of lesions were localized on the upper and lower limb. Also, in this following case series, there is a tendency for complete blood parameters, neutrophil-to-lymphocyte ratio (NLR), and absolute lymphocyte count (ALC) to be lower in mild cases of confirmed COVID-19 with skin manifestations. It can be concluded that COVID-19 infection may result in skin manifestation with various clinical presentations. This important manifestation may help in diagnosing and treating COVID-19 and prevent further transmission.